An unexpected benefit of pre-emptive rectal analgesic administration: the “key” to postoperative analgesia - Parlow, Joel L. (2000)
ANALGESIC AND ANTI-INFLAMMATORY DRUGS are frequently administered intraoperatively by the rectal route to provide pre-emptive postoperative analgesia. We report the case of an inmate of a federal penitentiary who underwent orthopedic surgery in a public hospital. After induction of general anesthesia, indomethacin and acetaminophen were administered rectally. This led to the incidental discovery of a handcuff key hidden in the rectum and, thereby, the prevention of a planned escape. A review of data regarding escapes by prisoners from public hospitals is provided, as well as a description of cases of patients presenting with foreign rectal objects. A number of benefits have been described for the use of pre-emptive analgesia. This is the first reported description of an incidental benefit: the prevention of a planned escape by a prison inmate.